Electrical and optical characterizations of a rotating gliding arc plasma-enhanced combustion dome in an aero-engine combustor. (2nd March 2021) - Hu, Changhuai; He, Liming; Chen, Yi; Zhao, Bingbing; Jun, Deng; Qu, Mei Jiao
Abstract: A gliding arc discharge is a typical method of producing non-equilibrium plasma, presenting excellent advantages in the field of enhanced combustion. In this study, a rotating gliding arc (RGA) plasma was combined with an aero-engine combustor dome to develop a RGA plasma-enhanced combustion dome. Experiments were conducted to investigate discharge, spectral, and infrared radiation temperature characteristics in the RGA plasma-enhanced combustion dome. Experimental results showed that two different discharge modes occurred during the RGA discharge process, the breakdown gliding mode and the steady arc gliding mode. The results had major implications for understanding the effects of the airflow rate and input voltage on the arc gliding mode transformation. The breakdown voltage, the average power, and the gliding arc rotational velocity increased with an increase in the airflow rate and a decrease of the input voltage. The spectral emission intensities of OH, O2, and O and vibrational temperature of N2 (C 3 Πu →B 3 Πg ) were relatively high at a high airflow rate. Additionally, the RGA discharge had a weak temperature rise effect on electrode, which had no obvious impact on the discharge process. These characteristics could be important for future applications for controlling plasma-enhanced combustion process.